2022
DOI: 10.36660/ijcs.20200113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atrial Fibrillation in Pacemaker Patients

Abstract: Background: Current pacemakers allow for the continuous recording of the occurrence of arrhythmic events. One of the most frequent arrhythmias after implantation of a device is atrial fibrillation (AF), an important risk factor for embolic events. The frequency of this arrhythmia in pacemaker patients has not been widely studied.Objectives: This study aimed to evaluate the prevalence, incidence, and predictors of the occurrence of AF in patients with double-chamber pacemakers and without a history of atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“… 13 Another study by Mario Augusto Cray da Costa documented that the prevalence of AF post-PPI was 25 %. 14 Multivariable logistic regression analysis showed that metabolic syndrome, age, coronary artery disease and systolic BP were good independent predictors of atrial arrhythmias among patients who underwent permanent pacemaker implantation. Metabolic syndrome is an important key factor in the final common pathway of the atrial fibrillation pathogenesis which includes atrial structural/electrical remodeling, inflammatory processes, along with cardiac autonomic changes.…”
Section: Discussionmentioning
confidence: 98%
“… 13 Another study by Mario Augusto Cray da Costa documented that the prevalence of AF post-PPI was 25 %. 14 Multivariable logistic regression analysis showed that metabolic syndrome, age, coronary artery disease and systolic BP were good independent predictors of atrial arrhythmias among patients who underwent permanent pacemaker implantation. Metabolic syndrome is an important key factor in the final common pathway of the atrial fibrillation pathogenesis which includes atrial structural/electrical remodeling, inflammatory processes, along with cardiac autonomic changes.…”
Section: Discussionmentioning
confidence: 98%
“…220 Em outro estudo de 186 portadores de marca-passo de um único centro no sul do Brasil [52% mulheres; mediana de idade, 67 anos (IIQ 57-76)], a prevalência de FA foi 25,3%, com incidência de 5,64 casos/100 pessoas-ano. 221 Entre os pacientes com doença cardiovascular que procuraram o setor de emergência, a prevalência de FA foi 40% daqueles com insuficiência cardíaca descompensada 222 e 44% daqueles com doença valvar cardíaca. 187 …”
Section: Comorbidades Associadasunclassified
“…220 In another study of 186 patients with pacemakers from a single center in Southern Brazil [52% women; median age, 67 years (IQR 57-76)], the prevalence of AF was 25.3%, with an incidence of 5.64 cases/100 persons-year. 221 Among patients with cardiovascular disease visiting the emergency department, the prevalence of AF was 40% of those with decompensated heart failure 222 and 44% of those with valvular heart disease. 187 …”
Section: Chapter 6 – Atrial Fibrillation and Atrial Fluttermentioning
confidence: 99%